A Reluctant Engagement: Alliances and Social Networks in Early-18th-Century Kespukwitk and Port Royal - Peace, Thomas (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2020)
Using a nominal census taken of the Mi’kmaq in 1708 and the Catholic parish records from the Acadian community of Port Royal, this paper revisits Acadian-Mi’kmaw relations at the beginning of the 18th century. Taken together, these sources illuminate Mi’kmaw reproduction in the areas around European settlement as well as family and social networks that linked these two societies. They reveal that the relationship between the Acadians and Mi’kmaq was stronger for some than for others. These were complex relationships determined by local conditions that varied depending on geography, family history, and economic activity.